Interactive Governance of Regulatory Reform in the Issuing of Building Construction Permits in DKI Jakarta - Aminatul Maula; Eko Prasojo (Magister Ilmu Administrasi Publik, 2021)
This study assessed interactive governance of regulatory reform in the implementation of integrated permit processing in the Investment Agency and One Stop Services (DPMPTSP). Interaction/coordination among regulatory reform actors in the integrated units was plagued by problems. Improvement in interactive governance was adopted to solve the problems in the regulatory reforms of processing building construction permits. The research was based on qualitative research design. Used Data collection techniques included in-depth interviews and desk research. Results showed that regulatory reforms in the processing of building construction permits in DPMPTSP, DKI Jakarta is influenced by rigidity of regulations, weak institutional functions, and inconsistency in central government policies. Weak institutionalization of interactive governance is the major obstacle that has hampered the implementation of regulatory reform in the building construction permits processing. Recommended course of action include strengthening institutional capacity, improving policy consistency between the central government and DKI Jakarta administration, and creating avenues that strengthen coordination and interaction among relevant actors